Fracture toughness of the stomatopod dactyl club is enhanced by plastic dissipation: a fracture micromechanics study - Chua, Isaiah Jia Qing (2022)
The dactyl club of stomatopods is a biological hammer used to strike on hard-shell preys. To serve its function, the club must be imparted with a high tolerance against both contact stresses and fracture. While the contact mechanics of the club has been established, fracture toughness characterization has so far remained more elusive and semi-quantitative using nanoindentation fracture methods. Here, we used microcantilever fracture specimens with a chevron-notched crack geometry to quantitatively evaluate the fracture response of the impact region of dactyl clubs. The chevron-notched geometry was selected as it minimizes surface-related artefacts due to ion milling, and further allows to carry out fracture tests on samples free of pre-cracks with stable crack propagation even for brittle materials. Both linear elastic as well as elastic-plastic fracture mechanics methods, together with finite element modelling, were employed to analyse the fracture data. We find that crack-tip plastic dissipation is the main mechanism contributing to the fracture properties of the dactyl club material. Our study also suggests that the chevron-notched crack geometry is a suitable method to quantitatively assess the fracture toughness of hard biological materials.